Development and evaluation of a hot-melt coating technique for enteric coating - Arun Trambak Patil; Deepak Shamrao Khobragade; Sandip Annaji Chafle; Amol Prasadrao Ujjainkar; Sudhir Niranjanrao Umathe; Champalal Laxminarayan Lakhotia (Universidade de São Paulo, 2012)
Conventional enteric coating requires the use of organic based polymers which are equally hazardous to the environment and operating personnel. Hot-melt coating avoids the use of solvents and is a safer and time-saving process. The present study was designed to assess the efficacy of hot-melt coating (HMC) as an enteric coating technique. Pellets prepared by extrusion spheronization were selected as the core formulation for a model of the gastric irritant drug diclofenac sodium (DFS) because of their innate advantages over single-unit formulations. Stearic acid (SA) and palmitic acid (PA) were evaluated as enteric hot-melt coating materials. HMC was carried out in a specially modified coating pan by applying SA and PA in molten state onto preheated pellets to achieve a coating level of 5-15 %w/w. Hot-melt coated pellets were evaluated for disintegration pH and in vitro dissolution in the pH range 1.2 to 6.8, along with basic micromeritics. SEM of coated pellets showed a uniform and smooth coating. These results indicated that HMC of both SA and PA exhibited very good enteric coating ability. The coated pellets showed negligible drug release in acidic pH. As the pellets were subsequently transferred to a higher pH level, a gradual increase in release of the drug from the pellets was observed with increasing pH of the dissolution media. The release was dependent upon coating extent, providing sustained enteric release as opposed to abrupt release with mixed release kinetics. O revestimento entérico convencional requer o uso de polímeros orgânicos os quais são igualmente danosos ao meio ambiente e ao pessoal que o executa. O revestimento por fusão a quente evita o uso de solventes e é processo mais seguro e que consome menos tempo. O presente estudo foi planejado para avaliar a eficácia do revestimento por fusão a quente (RFQ) como técnica de revestimento entérico. Os péletes preparados por esferonização por extrusão foram selecionados como formulação central para modelo de fármaco irritante gástrico, o diclofenaco sódico (DFS) em razão das vantagens inerentes sobre as formulações de única dose. O ácido esteárico (AE) e o ácido palmítico (AP) foram avaliados como materiais para o revestimento de fusão a quente. O RFQ foi realizado em recipiente especialmente modificado, aplicando AS e PA no estado fundido em péletes pré-aquecidos para atingir nível de revestimento de 5 a 15% p/P. Os péletes revestidos por fusão a quente for avaliados quanto ao pH de desintegração e à dissolução in vitro na faixa de pH de 1,2 a 6,8, juntamente com base micromerítica. O SEM dos péletes revestido mostrou revestimento uniforme e plano. Esses resultados indicaram que o RFQ tanto do AE quanto do AP apresentou capacidade de revestimento muito boa. Os péletes revestidos mostraram pouca liberação do fármaco em pH baixo. Como os péletes foram, subsequentemente, transferidos para pH mais altos, observou-se aumento gradual na liberação do fármaco dos péletes com o aumento do pH do meio de dissolução. A liberação foi dependente da extensão do revestimento, sendo a liberação entérica controlada, contrariamente à liberação abrupta com cinéticas mistas.